Effectof Herbal Extract-Supplemented Feeds On Oxidative Stress, Biochemical Markers And Production Performance In Jabalpur Colour Layer Birds (Applied Biological Research, 2014)
The present study was aimed to evaluate the impact of ginger, cinnamon  bark, chicory and stevia extract-supplemented feeds on serum clinical  biochemistry and production performance in Jabalpur colour birds. Fifty  four birds of 32 weeks age were randomly divided into 9 groups of 6 birds  each. Control group was fed normal basal feed whereas rest groups were  fed on feeds supplemented with alcoholic extracts of various herbs  separately at 2 levels each [ginger, cinnamon and stevia extract mixed with  feed @ 2.5 and 5.0 g kg-1feed and chicory extract @ 1.25 and 2.5 g kg-1 feed]. Blood samples, collected on 0, 14, 28, 42 and 56th day of treatment,  revealed a non-significant decrease in lipid peroxidase and non-significant  increase in superoxide dismutase activity in birds of treatment groups.  Reduced glutathione showed significant increase in all the treatment  groups with higher value in birds fed with chicory (2.5 g kg-1) and  cinnamon (5 g kg-1) supplemented feed, respectively. Glucose-6-phosphate  dehydrogenase showed significant increase from days 0 to 56 in all the  treatment groups. Alanine aminotransferase and aspartate aminotrans ferase showed a decreasing trend and significant lowering effect was noticed in birds fed with chicory and ginger. The serum creatinine showed  significantly low value in chicory (2.5 g kg-1) fed birds. No significant  variation was observed in blood urea nitrogen. Increase in egg weight was  significant higher in treatment groups with highest increase in ginger @ 5  g kg-1 fed birds. The supplementation of herbal drugs increased body  weight significantly as the interval of time increased up to 56th days with  highest weight in birds fed with chicory @ 2.5 g kg-1feed.
Keywords: Blood urea nitrogen; chicory; cinnamon; creatinine; ginger; oxidative stress; stevia; superoxide dismutase